The Hikmah Model as a Means for Interconvictional Dialogue and Citizenship Education in Francophone (Belgian) Secondary Education - Lafrarchi, Naïma (Religious education, 2023)
Much attention has been given to interreligious dialogue in recent decades. However, less attention has been devoted to models that support citizenship through Islamic religious education in secondary education. Based on Lipman’s Philosophy for Children, Hashim developed the Hikmah model. This model contributes to cognitive, social, and affective skills of Muslim pupils. A theoretical framework regarding interreligious education and the Hikmah model exploring the didactic opportunities is given. The explorative qualitative research aims to explore the potential of the Hikmah model for Islamic religious education (IRE) in Francophone secondary education.